Economic and welfare influences of an energy excise tax in Jiangsu province of China: A computable general equilibrium approach. (20th February 2019) - Peng, Jiao-Ting; Wang, Yuan; Zhang, Xiang; He, Yanmin; Taketani, Masashi; Shi, Rui; Zhu, Xiao-Dong
Abstract: In recent years, although China's energy intensity has gradually decreased, the total consumption of energy commodities has increased sharply. Levying an excise tax on energy commodities is one of the keys to control energy consumption. This paper constructed a Computable General Equilibrium model to simulate levying an energy excise tax in Jiangsu province, which is one of China's strong economic provinces with lower endowments of energy resources. The results show that the energy excise tax is beneficial for energy saving, while levying energy will cause economic and welfare declines. When at a level tax rate of 5%, 10%, and 15%, the loss of GDP will reach 0.27%, 0.66%, and 1.13% respectively, and the incomes of inhabitants and enterprises alike will decrease. When the energy tax revenue used to compensate for the welfare losses suffered by inhabitants or enterprises, there is a double dividend effect (energy saving and increasing income). Moreover, the simulation indicated that a 5% improvement of energy efficiency brings about a "backfire" phenomenon, with an increase of 142% in energy consumption. However, when considering the cost of energy-efficiency improvements, the rebound effect will be significantly decreased. Policy suggestions are further recommended to help improve the energy policy in regard to reducing energy consumption. Highlights: CGE model is proposed to evaluate the effect of energy excise tax. Levying energy excise tax with refund measures could result in a double dividend. The rebound effect of energy efficiency improvement is quantified.